2022
DOI: 10.1136/bmjoq-2021-001710
|View full text |Cite
|
Sign up to set email alerts
|

Reducing low-value care: what can we learn from eight de-implementation studies in the Netherlands?

Abstract: BackgroundReducing the overuse of care that is proven to be of low value increases the quality and safety of care. We aimed to identify lessons for reducing low-value care by looking at: (1) The effects of eight de-implementation projects. (2) The barriers and facilitators that emerged. (3) The experiences with the different components of the projects.MethodsWe performed a process evaluation of eight multicentre projects aimed at reducing low-value care. We reported the quantitative outcomes of the eight proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…(46) However, in order to overcome the powerful underlying drivers associated with low-value care, it was recognized that problem analysis and context assessment were fundamental to tailoring de-implementation strategies. (45,46) This exercise was made possible in our study through usability testing, which enabled us to re ne the intervention with interested parties to strengthen the ability of trauma teams to de-implement the targeted practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(46) However, in order to overcome the powerful underlying drivers associated with low-value care, it was recognized that problem analysis and context assessment were fundamental to tailoring de-implementation strategies. (45,46) This exercise was made possible in our study through usability testing, which enabled us to re ne the intervention with interested parties to strengthen the ability of trauma teams to de-implement the targeted practices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have showed favorable outcomes associated with de-implementation interventions (45,46,(49)(50)(51) including a recent review of RCTs that found a signi cant median relative reduction of 17% in low-value care. (46) However, a greater number of interventions tailored to contextual factors, as in our study, were recognized as a potential strategy for further increasing their impact on lowvalue care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was performed as part of a national program aimed at reducing LVC. 18 Within the scope of this overarching program, a systematic review of the literature on deimplementation was performed, which is used as a basis for this manuscript. The review protocol has not been registered or published.…”
Section: Methodsmentioning
confidence: 99%